„Wiara i poszukiwanie Boga". Lumen fidei w perspektywie teologii religii - Ferdek, Bogdan (Poznańskie Studia Teologiczne, 2014)
Lumen Fidei (The Light of Faith) is intended as the guiding magisterial document for the Year of Faith. Faith is the gateway to salvation. To reach eternal salvation, it is necessary: to have been baptized sacramentally; and to die sincerely professing the Catholic faith. A U.S. Jesuit priest, poet, lyricist, and essayist Leonard Edward Feeney (1897-1978) articulated and defended a strict interpretation of the Roman Catholic doctrine, extra Ecclesiam nulla salus (outside the Church there is no salvation). He took the position that baptism of blood and baptism of desire are unavailing and that therefore no non-Catholics will be saved. Fighting against what he perceived to be the liberalization of Catholic doctrine, he came under ecclesiastical censure. The Vatican’s Holy Office rejected his restrictive view by distinguishing between those who really belong to the Church (in re) and those who belong by desire (in voto). The desire would be explicit in those who were catechumens and implicit in those people of goodwill who would join the Church if they knew it to be the one true Church of Christ. St. Augustine also distinguishes between the sacrament of baptism and the turning of the heart to God. He teaches that if either of these conditions cannot be secured, the other will be sufficient. A baptized child is saved without turning its heart to God, should it die before coming to the age of reason, and a man who turns his heart to God is saved without water baptism, provided he in no way despises the sacrament. St. Thomas states, „some have received the invisible sanctification without visible sacraments, and to their profit; but though it is possible to have the visible sanctification, consisting in a visible sacrament, without the invisible sanctification, it will be to no profit”. The encyclical Lumen Fidei presents faith as a light that dispels the darkness and illuminates the way which is the human being. Respecting the religious sensibility of searchers who lack explicit faith, the letter recognizes that “Religious man strives to see signs of God, in the daily experiences of life, in the cycle of the seasons, in the fruitfulness of the earth and in the movement of the cosmos” (no. 35). It continues, “To the extent that they are sincerely open to love and set out with whatever light they can find, the popes tell us, “[searchers] are already, even without knowing it, on the path leading to faith.” The light of faith in Jesus illumines the path of seekers. Letter to the Hebrews speaks about Enoch and Abel who believed in God before Abraham. Christ is the concentration of light of God, who illumines every human experience and journey of man to God.